(untitled) (Kathmandu University Medical Journal, 2014)
Lipomas are the most common benign mesenchymal tumour. Thirteen percent of lipomas are seen in head and neck region. Anterior neck lipoma is a rare one. Anterior neck lipoma with mediastinal extension is extremely rare. We are presenting a case of 52 years old male reported to Central Referral Hospital, Sikkim Manipal Institute of Medical Sciences, Gangtok, Sikkim with complains of swelling in left side of neck for last 18 months along with occasional history of dyspnoea. Physical examination, ultrasound, computed tomography and fine needle aspiration cytology are in favor of lipoma. Due to its location up to the anterior mediastinum, the surgery could not be done in this hospital and patient was referred to higher center having cardio-thoracic surgical back up. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11048 Kathmandu University Medical Journal Vol.11(1) 2013: 88-90